Extracorporeal Membrane Oxygenation to Support Life-Threatening Drug-Refractory Electrical Storm. Issue 10 (October 2020) - Baudry, Guillaume; Sonneville, Romain; Waintraub, Xavier; Lebreton, Guillaume; Deguillard, Camille; Mertens, Emilie; Bouadma, Lila; Demondion, Pierre; Bréchot, Nicolas; Luyt, Charles-Edouard; Extramiana, Fabrice; Hékimian, Guillaume; et al.
Abstract : Objectives: Despite rapid implementation of anti-arrhythmic treatment and sedation and controlling the triggering event, rare patients develop treatment-refractory electrical storm and their hemodynamic instability prevents emergency catheter ablation. In that context, venoarterial extracorporeal membrane oxygenation could rapidly restore hemodynamics and tissue perfusion and reduce myocardial oxygen consumption, until adequate anti-arrhythmic drug levels are reached to safely perform catheter ablation. Design: Retrospective, multicenter study over an 8-year period. Setting: Two French tertiary care centers. Patients: Eighty-three consecutive adults with venoarterial extracorporeal membrane oxygenation-supported treatment-refractory electrical storm (median [interquartile range] age, 55 yr [48–63 yr]). Measurements and Main Results: Fifty-nine percent of these patients had acute ischemic cardiomyopathy and 66% underwent cardiopulmonary resuscitation prior to venoarterial extracorporeal membrane oxygenation initiation, with 18% cannulated during it. Fifty patients (60%) had ventricular tachycardia and/or ventricular fibrillation alternating with short periods of sinus rhythm and 33 (40%) had refractory ventricular tachycardia and/or ventricular fibrillation. Twelve patients (15%) underwent safe catheter ablation under venoarterial extracorporeal membrane oxygenation. After a median of 3 days (1–13 d) on extracorporeal membrane oxygenation support, 37 patients (45%) were successfully weaned off and 42% were alive 6 months post-ICU admission. Multivariable analysis retained ventricular tachycardia and/or ventricular fibrillation episodes alternating with short periods of sinus rhythm (odds ratio, 0.18; 95% CI, 0.06–0.52; p = 0.002) and age less than 50 years (odds ratio, 0.32; 95% CI, 0.18–0.89; p = 0.002) as being independent protective factors with 6-month survival, regardless of the underlying electrical storm cause. Conclusions: Among venoarterial extracorporeal membrane oxygenation-supported drug-refractory electrical storm patients, 42% survived 6 months post-ICU admission. Ventricular tachycardia and/or ventricular fibrillation episodes alternating with short periods of sinus rhythm and age less than 50 years were independently associated with better survival.